An analysis of the situation of community schools in Bangladesh - Kalam, Md. Abul; Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2020)
Contributing towards a strengthening of the government's Universal Primary Education Programme- Education For All- by the year 2000, has been one of the important aims of BRAC education programme. To materialize this aim BRAC has been providing Non- Formal Primary Education to the 'out of school' and 'out of reach' students, for more than a decade. Apart from this, BRAC education programme started, though in a small scale. its own formal primary schools very recently. In course of operating its education programme, BRAC has established a relationship with the education departments of the government. specially Directorate of Non-formal Education (DNFE). The community school programme is the most recent addition to such collaborative programmes. The government officially handed over 67 non-functioning community schools to BRAC by the end of 1998, of which 33 have already been started by BRAC. This study attempted to assess the situation of these non-functioning community schools. The objectives of the study were 10: i) assess current and previous condition of community schools; ii) know more about the quality of teachers; iii) prepare a learners' profile; iv) document the causes of non-functioning of the community schools; and v) obtain information for future evaluation.